Insect eggs induce a systemic acquired resistance in Arabidopsis. (December 2014) - Hilfiker, Olivier; Groux, Raphaël; Bruessow, Friederike; Kiefer, Karin; Zeier, Jürgen; Reymond, Philippe
Summary Although they constitute an inert stage of the insect's life, eggs trigger plant defences that lead to egg mortality or attraction of egg parasitoids. We recently found that salicylic acid (SA) accumulates in response to oviposition by the Large White butterfly Pieris brassicae, both in local and systemic leaves, and that plants activate a response that is similar to the recognition of pathogen‐associated molecular patterns (PAMPs), which are involved in PAMP‐triggered immunity (PTI). Here we discovered that natural oviposition by P. brassicae or treatment with egg extract inhibit growth of different Pseudomonas syringae strains in Arabidopsis through the activation of a systemic acquired resistance (SAR). This egg‐induced SAR involves the metabolic SAR signal pipecolic acid, depends on ALD1 and FMO1, and is accompanied by a stronger induction of defence genes upon secondary infection. Although P. brassicae larvae showed a reduced performance when feeding on Pseudomonas syringae‐infected plants, this effect was less pronounced when infected plants had been previously oviposited. Altogether, our results indicate that egg‐induced SAR might have evolved as a strategy to prevent the detrimental effect of bacterial pathogens on feeding larvae.